Effect of orthopaedic resident education on screening for intimate partner violence - Mikaela J. Peters; Darren M. Roffey; Kelly A. Lefaivre (BMC, 2021)
Abstract Background Intimate Partner Violence (IPV) is prevalent in women presenting to orthopaedic fracture clinics. Rates of IPV have increased during the COVID-19 global pandemic. Our aim was to determine the effect of educational experiences on IPV knowledge and IPV screening to inform best-practices in resident education. Methods Cross-sectional online survey of orthopaedic surgery residency programs in Canada. Demographics, IPV educational experiences, IPV knowledge, and frequency of IPV screening were collected via a modified version of the Physician Readiness to Manage Intimate Partner Violence Survey (PREMIS). Descriptive statistics and regression modeling identified predictors of IPV knowledge and frequency of IPV screening. Results Responses were obtained from 105 orthopaedic residents; 84% participated in classroom training, 39% underwent mentorship training, 32% received both classroom training and mentorship, and 10% reported neither. Classroom training had no statistically significant association with IPV knowledge or frequency of IPV screening. Residents who received mentorship were 4.1 times more likely to screen for IPV (95% CI: 1.72-10.05), older residents were more likely to screen for IPV (OR: 8.3, 95% CI: 2.64-29.84), and senior residents were less likely to screen for IPV than junior residents (OR: 0.29, 95% CI: 0.09-0.82). Conclusions Classroom training was not associated with any effect on IPV knowledge nor the frequency of IPV screening. Educational efforts should be targeted at increasing mentorship opportunities in order to improve IPV screening practices in Canadian orthopaedic residents.